Profiling of the immune repertoire in COVID-19 patients with mild, severe, convalescent, or retesting-positive status. Issue 118 (March 2021) - Zhou, Yonggang; Zhang, Jinhe; Wang, Dongyao; Wang, Dong; Guan, Wuxiang; Qin, Jingkun; Xu, Xiuxiu; Fang, Jingwen; Fu, Binqing; Zheng, Xiaohu; Wang, Dongsheng; Zhao, Hong; et al.
Abstract: Forty-seven samples of peripheral blood mononuclear cells from four groups of coronavirus disease (COVID)-19 patients (mild, severe, convalescent, retesting-positive) and healthy controls were applied to profile the immune repertoire of COVID-19 patients in acute infection or convalescence by transcriptome sequencing and immune-receptor repertoire (IRR) sequencing. Transcriptome analyses showed that genes within principal component group 1 (PC1) were associated with infection and disease severity whereas genes within PC2 were associated with recovery from COVID-19. A "dual-injury mechanism" of COVID-19 severity was related to an increased number of proinflammatory pathways and activated hypercoagulable pathways. A machine-learning model based on the genes associated with inflammatory and hypercoagulable pathways had the potential to be employed to monitor COVID-19 severity. Signature analyses of B-cell receptors (BCRs) and T-cell receptors (TCRs) revealed the dominant selection of longer V–J pairs (e.g., IGHV3-9–IGHJ6 and IGHV3-23–IGHJ6) and continuous tyrosine motifs in BCRs and lower diversity of TCRs. These findings provide potential predictors for COVID-19 outcomes, and new potential targets for COVID-19 treatment. Highlights: Outline the immune response of COVID-19 patients with mild, severe, convalescent, or retesting-positive status. A dual-injury mechanism based on inflammatory and hypercoagulable pathways reveals the cause of COVID-19 severity. Establish an AI model for screening potential predictors of COVID-19 severity based on the dual-injury mechanism. Longer CDR-H3 loops of the BCR and more concentrated TCR have the potential to evaluate host immunity against the SARS-CoV-2.